Correlation Between the Dependency and Quality of Life of Children with Cerebral Palsy - victor, Agnes (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Cerebral palsy is one of the neuro developmental disorders with many problems such as physical, functional, psychological, social and financial, as they are dependent upon caregivers on every activity. When these parents learn that their child has cerebral palsy, it distresses them. Even though caring for a child without a disability requires significant resources, these demands are frequently higher. Additionally, psychosocial issues in children with cerebral palsy increases the care burden. The objectives of the study were to correlate the level of dependency and quality of life of children with cerebral palsy before and after intervention. Methods: The study was conducted in Pediatric Rehabilitation Department, ‘King Abdullah Specialist Children’s Hospital, National Guard Health Affairs, Riyadh. The study subjects were the children with cerebral palsy aged 4-12 years along with their caregivers. The researcher had chosen the descriptive study design. 30 children with cerebral palsy were selected using purposive sampling technique. Results & Discussion: Showed that there was a highly significant association at p<0.001 level between the overall quality of life and the level of dependency in the study group. Conclusion: There was an association between level of dependency and the overall quality of life among children with Cerebral palsy.